INHERITED SILENCE AND DIASPORIC IDENTITY FORMATION IN HALA ALYAN’S SALT HOUSES - Sara Magdi Mamdouh Salama; Lili Awaludin; Yoga Sudarisman (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2026)
In studies of diasporic literature, Salt Houses by Hala Alyan has frequently been examined through the lenses of trauma, displacement, and memory. However, less attention has been given to how silence operated as a mechanism through which these experiences were transmitted across generations. This study examined how inherited silence functioned not merely as the absence of speech, but as a force shaping memory, emotion, and diasporic identity. Tracing a Palestinian family across generations, the novel presented quietness and narrative gaps as embedded in both narrative form and everyday interaction. Drawing on Marianne Hirsch’s concept of postmemory and Stuart Hall’s theory of cultural identity, this study employed qualitative close reading of narrative gaps and silences within the text. The findings showed that the selective withholding of family history, emotional restraint, and epistemic gaps shaped the transmission of memory and the negotiation of diasporic identity across generations. More broadly, this study positioned silence as a communicative mode of transmission that extended existing discussions of postmemory and trauma beyond explicit narration and representation. By foregrounding silence as an active structure rather than a simple absence, this study contributed to broader discussions of intergenerational memory, diasporic belonging, and cultural identity formation. The study was limited to one literary text, which may have restricted broader generalizability.